Application of microalgae in wastewater: opportunity for sustainable development - Ramírez Mérida, Luis G.; Rodríguez Padrón, Richard A. (Frontiers in Environmental Science, 2023)
1 Introduction Industrial sustainability is a process that has been gaining space in recent years. The use of microalgae for wastewater treatment could solve some environmental challenges, optimize resources, and generate value-added products in agriculture, biofuel, food, and feed. The use of High Rate Algal Pond (HRAP) presents economic benefits, by treating contaminated effluents and taking advantage of the microalgae biomass generated. The microalgae growth in wastewater can be limited by lighting energy or the easily assimilable carbon source, due to the high load of nutrients and organic matter present in these effluents. In the same way, other physical, chemical, and biological parameters must be controlled to guarantee that the process reaches its maximum performance. The technology applied with microalgae for the waste industrial treatment seeks to generate sustainable, economical, and efficient processes that guarantee the discharge of water under standard parameters that allow for preserving the environment, the quality of life of citizens and generating inputs such as biofertilizers that allow avoiding crucial problems such as NPK ratio imbalance, soil hardening, salinization, nutrient depletion, groundwater contamination and food for animal consumption that allows generating nutritional alternatives. In this way, the treatment of wastewater with microalgae is an opportunity to solve sanitary and environmental problems under a sustainable approach to obtain inputs, although some challenges must be solved for scale production. This document intends to show outstanding aspects related to effluent treatment, water reuse, and sustainable production of agricultural inputs through the use of microalgae.